Varioloid A, a new indolyl-6,10b-dihydro-5aH-[1]benzofuro[2,3-b]indole derivative from the marine alga-derived endophytic fungus Paecilomyces variotii EN-291 - Zhang, Peng; Li, Xiao-Ming; Mao, Xin-Xin; Mándi, Attila; Kurtán, Tibor; Wang, Bin-Gui (Beilstein Journal of Organic Chemistry, 2016)
A new indolyl-6,10b-dihydro-5aH-[1]benzofuro[2,3-b]indole derivative, varioloid A (1), was isolated from the marine alga-derived endophytic fungus Paecilomyces variotii EN-291. Its structure was elucidated on the basis of extensive analysis of 1D and 2D NMR data and the absolute configuration was determined by time-dependent density functional theory-electronic circular dichroism (TDDFT-ECD) calculations. A similar compound, whose planar structure was previously described but the relative and absolute configurations and 13C NMR data were not reported, was also identified and was tentatively named as varioloid B (2). Both compounds 1 and 2 exhibited cytotoxicity against A549, HCT116, and HepG2 cell lines, with IC50 values ranging from 2.6 to 8.2 µg/mL.
Keywords: bisindolyl benzenoid derivatives; cytotoxicity; marine alga-derived fungus; Paecilomyces variotii; TDDFT-ECD calculation